The Cambridge economic history of modern Britain - Floud, Roderick; Humphries, Jane 1948-; Johnson, Paul (Paul A.) (Cambridge University Press, 2014)
"A new edition of the leading textbook on the economic history of Britain since industrialisation. Leading historians and economists examine the foundational importance of economic life in modern Britain as well as the close interconnections between economic, social, political and cultural change. Each chapter provides a clear guide to the major controversies in the field and students are shown how to connect historical evidence with economic theory and how to apply quantitative methods. Volume 1, on 1700-1870, offers new approaches to classic issues such as the causes and consequences of industrialisation, the role of institutions and the state, and the transition from an organic to an inorganic economy, as well as introducing new issues such as globalisation, convergence and divergence, the role of science, technology and invention, and the growth of consumerism. Throughout the volume, British experience is set within an international context and its performance benchmarked against its global competitors"--Provided by publisher.